2016
DOI: 10.1016/j.paid.2016.03.082
|View full text |Cite
|
Sign up to set email alerts
|

Support for a general factor of well-being

Abstract: Abstract. Well-being is typically defined as positive feeling (e.g. happiness), positive functioning (e.g. competence, meaning) or a combination of the two. Recent evidence indicates that well-being indicators belonging to different categories can be explained by single "general" factor of well-being (e.g. Jovanovic, 2015). We further test this hypothesis using a recent well-being scale, which includes indicators of positive feeling and positive functioning (Huppert & So, 2013). While the authors of the scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
3
23
1
1
Order By: Relevance
“…Specifying a higher-order factor structure that consisted of five lower-order factors did not improve the model fit. These findings suggested that SWB as measured by the 29-item WeBS should not be considered as comprising a single general factor, contrary to preliminary results from a recent study (Longo et al, 2016). Rather, our results showed that the confirmatory bifactor structure was a more appropriate fit with the data.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Specifying a higher-order factor structure that consisted of five lower-order factors did not improve the model fit. These findings suggested that SWB as measured by the 29-item WeBS should not be considered as comprising a single general factor, contrary to preliminary results from a recent study (Longo et al, 2016). Rather, our results showed that the confirmatory bifactor structure was a more appropriate fit with the data.…”
Section: Resultscontrasting
confidence: 99%
“…These five domains of SWB are theorized to be orthogonal to each other; for example, people who enjoy high levels of social well-being can have either high or low levels of eudaimonic well-being and hedonic well-being. Consistent with emerging evidence, this organization of SWB suggests a bifactor structure of this variable, in which a general factor of overall well-being as well as five domain-specific factors can be extracted (Chen, Bai, Lee, & Jing, 2016;de Bruin & du Plessis, 2015;Jovanovic´, 2015;Longo et al, 2016). Conceptually, such a complex representation of SWB implies that the construct can be conceptualized not only as a broad representation of people's overall psychological functioning but that it also can manifest in several domains of people's lives.…”
Section: Multidimensional Conceptualization and Measurement Of Swbsupporting
confidence: 69%
“…9 However, the structure of well-being has been debated recently, 10,11 and empirical research suggests that these are distinct approaches to well-being but not distinct constructs; thus, they are better represented by single 'general' factor of well-being. [12][13][14] Accordingly, mental health and illness are not extremes of one continuum but distinct (although correlated) continua. 4 The two-continua model posits one continuum indicating level of mental health, while the other refers to the presence or absence of mental illness.…”
mentioning
confidence: 99%
“…both on a scale of 0-10. Similar to Longo, Coyne, Joseph, and Gustavsson (2016), the happiness and satisfaction measures used were highly correlated (r=0.79), and were therefore averaged to create a single well-being variable. To measure income, respondents reported whether their annual household income fell into one of eight categories: Less than £25,000, £25,000 to £34,999, £35,000 to £49,999, £50,000 to £74,999, £75,000 to £99,999, £100,000 to £149,999, £150,000 or more, or "Prefer not to say".…”
Section: Methodsmentioning
confidence: 99%